Multi-stage crosslinking organic boron crosslinking agent capable of resisting high temperature of 180 DEG C and preparation method of multi-stage crosslinking organic boron crosslinking agent
Through the complex cross-linking reaction between the multi-stage cross-linked organic boron cross-linking agent and the fracturing fluid, the instability and high friction problems of the existing high-temperature resistant boron cross-linking agent in deep well fracturing fluid are solved, and efficient Improved temperature resistance and construction performance.
Patent Information
- Application Number
- CN202411431420.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-21
AI Technical Summary
The existing high-temperature resistant boron crosslinking agents have problems such as unstable, easy precipitation, high construction friction resistance, poor temperature resistance and fast crosslinking in the deep well fracturing fluid, which is difficult to meet the construction requirements of high-temperature deep well fracturing fluid.
The organic boron cross -linked agent with multi -level cross -linking cross -linking, through components such as boron -containing polymerization monomer, borate, and boron -containing compounds to chelate, forming a boron carrier with different release speeds, and multi -level cross -linking cross -linking the fracture liquid , Slowly forming glue, enhancing the spatial structure and mechanical stability of frozen glue.
The temperature resistance of the fracturing fluid is significantly improved, enabling it to work stably at high temperatures of 180°C, reducing construction friction, extending the cross-linking time, and improving the sand-carrying performance and gel-breaking performance.
Smart Images

Figure CN119331594A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an organic boron crosslinking agent, and more specifically to a multi-stage crosslinking organic boron crosslinking agent resistant to high temperature of 180°C and a preparation method thereof. Background Art
[0002] With the continuous development of oilfield mining technology, the easily recoverable reserves of oilfields are becoming less and less. At present, the exploration and development of deep well oil and gas reservoirs has become the focus of research. Due to the high temperature and low porosity of deep well formations, higher requirements are placed on the temperature resistance and shear resistance of fracturing fluids.
[0003] Crosslinking agent is an important component of water-based fracturing fluid. It forms a high-viscosity gel by complexing with polymers in various bond states, so as to meet the needs of seam creation, sand carrying, and friction reduction in fracturing fluid construction. In the early 1990s, high-temperature resistant organic boron crosslinking agents developed rapidly, and there were many organic boron delayed crosslinking fracturing fluids with a temperature resistance of about 150°C. Schlumberger's boron crosslinking fracturing fluid patent (US5445223) uses polymers to encapsulate boron ions to control the delayed crosslinking time and improve the temperature resistance. Its temperature resistance can reach 176°C, but there are no reports on series products and mine applications. my country began to develop high-temperature resistant boron crosslinking agents in the mid-1990s and began to use them in some oil fields. These crosslinking agents have many defects: instability, easy precipitation, high construction friction, poor temperature resistance, and fast crosslinking, which cannot meet the construction requirements of fracturing fluids. Patent CN202211637213.6 discloses a method for preparing an organic boron crosslinking agent, which can crosslink low-concentration guar gum under acidic conditions, but does not explain its delayed crosslinking time, and its temperature resistance is only 60°C, which is not suitable for high-temperature deep well fracturing; Patent CN201510164955.5 discloses a boron crosslinking agent and a boron crosslinking fracturing fluid for high-temperature deep wells, with an adjustable crosslinking time of 3 to 10 minutes, good heat resistance and shear resistance and other properties, but it still has some problems, such as the use of conventional ligands and two-stage chelation methods, the crosslinking strength is sensitive to the concentration of the crosslinking agent, the use range of the crosslinking agent is narrow, which is not conducive to the dosage control during on-site use, and the maximum temperature resistance is 175°C. These crosslinking agent crosslinked guar gum fracturing fluids still have considerable problems in achieving the functions of improving sand carrying performance, reducing construction friction, ensuring gel breaking performance, reducing costs, and reducing reservoir damage. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a multi-stage cross-linked organic boron cross-linking agent resistant to high temperatures of 180°C and a preparation method thereof. After the cross-linking agent is compounded with the fracturing fluid, boron carriers with different release rates are opened layer by layer, releasing borate ions to cross-link with the fracturing fluid in multiple stages and slowly gelling, thereby enhancing the spatial structure and mechanical stability of the frozen gel, and greatly improving the temperature resistance of the fracturing fluid.
[0005] The technical solution adopted by the present invention to solve the technical problem is: construct a multi-stage cross-linking organic boron cross-linking agent resistant to high temperature of 180°C, including the following components with a total mass fraction of 100 parts:
[0006] Boron-containing polymer monomer: 3-4 parts;
[0007] Boric acid ester: 10-12 parts;
[0008] Boron-containing compound: 2-3 parts;
[0009] Solvent 1: 15-18 parts;
[0010] Solvent 2: 2-3 parts;
[0011] First ligand: 0.5-1 part;
[0012] Second ligand: 13-15 parts;
[0013] The third ligand: 20-25 parts;
[0014] Alkenyl oxygen-containing silane: 1 to 1.5 parts;
[0015] Strong hydrophilic monomer: 2-3 parts;
[0016] Initiator: 0.3-0.5%, 0.015-0.035 parts by weight of the total weight of boron-containing polymerization monomer and strong hydrophilic monomer;
[0017] The remainder was deionized water.
[0018] In the above scheme, the boron-containing polymerizable monomer is any one of allylboronic acid pinacol ester, vinylboronic acid pinacol ester, 1-phenylvinylboronic acid, cis-propyleneboronic acid, 3-vinylbenzeneboronic acid or 1-buteneboric acid.
[0019] In the above scheme, the borate ester is any one of trimethyl borate, triethyl borate or triisopropyl borate.
[0020] In the above scheme, the boron-containing compound is any one of borax, boric acid or sodium borate.
[0021] In the above scheme, the first ligand is one of nano graphene oxide and nano fumed silica;
[0022] The second ligand is any one of monoethanolamine, triethanolamine, ethylenediamine, acetylacetone, Schiff base, sodium gluconate, citric acid, diethylenetriaminepentaacetic acid, and N-hydroxyethylenediamine;
[0023] The third ligand is any one of pinacol, xylitol, mannitol, sorbitol and polyvinyl alcohol.
[0024] In the above scheme, the first solvent is one of methanol, ethanol and ethylene glycol; the second solvent is one of isopropanol and n-butanol.
[0025] In the above scheme, the alkenyl oxygen-containing silane is any one of dimethylvinylethoxysilane, methylvinyldiethoxysilane, allyltriethoxysilane and vinyltri(2-methoxyethoxy)silane.
[0026] In the above scheme, the strong hydrophilic monomer is one of fumaric acid and maleic acid;
[0027] In the above scheme, the initiator is a combination system of potassium persulfate and sodium bisulfite, and the mass ratio of potassium persulfate to sodium bisulfite is 3:2.
[0028] The present invention also provides a method for preparing the multi-stage cross-linking organic boron cross-linking agent resistant to high temperature of 180° C., comprising the following steps:
[0029] S1: Preparation of the first intermediate:
[0030] Add solvent 1 and the first ligand to the enamel reaction kettle, stir evenly and then perform ultrasonic oscillation dispersion for 15 minutes to 30 minutes to obtain a ligand-solvent suspension; add alkenyl oxygen-containing silane to the reaction kettle, react for 1 hour to 2 hours at a reaction kettle temperature of 20°C to 25°C and a stirring speed of 300r / min to 400r / min to perform surface modification on the first ligand; maintain the stirring speed unchanged, add a strong hydrophilic monomer, a boron-containing polymerization monomer and an initiator to the solution, react at 35°C to 40°C for 2 to 3 hours, and obtain a first intermediate by surface graft polymerization;
[0031] S2: Preparation of the second intermediate:
[0032] Add solvent 2, borate ester and W1 weight of the second ligand into the batching kettle, react for 1h to 1.5h at a temperature of 60°C to 70°C and a stirring speed of 200r / min to 300r / min, transfer all the reaction products in the batching kettle into an enamel reactor, add W2 weight of the second ligand, mix well with the first intermediate, react for 1h to 1.5h at a temperature of 60°C to 70°C and a stirring speed of 300r / min to 400r / min to obtain a second intermediate;
[0033] S3: Preparation of the third intermediate:
[0034] The reactor temperature is set at 70°C to 80°C, the stirring speed is 700r / min to 800r / min, and the third ligand by weight W3 is slowly added to the second intermediate, and the mixture is stirred and dissolved. The mixture is reacted at a stirring speed of 300r / min to 400r / min for 1h to 1.5h to obtain the third intermediate;
[0035] S4: Final product preparation:
[0036] Keeping the temperature and stirring speed of the reactor unchanged, add the boron-containing compound to the third intermediate, stir and mix to dissolve, add W4 weight of the third ligand, continue to react for 1h to 1.5h, add water to dilute, obtain the final product, cool and discharge, which is the multi-stage cross-linked organic boron cross-linking agent resistant to high temperature of 180°C;
[0037] The ratio of W1 to W2 in the step S2 is 3:7 to 4:6; the ratio of W3 in the step S3 to W4 in the step S4 is 8:2 to 9:1.
[0038] In the above scheme, any one of the first intermediate, the second intermediate, the third intermediate and the final product can be used as an organic boron crosslinking agent. From the first intermediate to the final product, the crosslinking agent's delay performance, crosslinking strength and crosslinking fracturing fluid performance are gradually improved.
[0039] In the above scheme, the multi-stage cross-linked organic boron cross-linking agent can be compounded with high temperature resistant fracturing fluid and applied to the fracturing construction of high temperature deep wells.
[0040] The mechanism of action of the present invention is as follows: the surface of a boron-containing polymer monomer is grafted and copolymerized onto the surface of a nano material to obtain a boron-containing small molecule polymer, and then the boron-containing small molecule polymer, borate ester, boron-containing compounds, etc. are chelated step by step by a variety of chelating agents to achieve step-by-step encapsulation and multi-element chelation of organic boron to obtain boron carriers with different release rates, and the multi-stage released borate ions are graded and cross-linked with the fracturing fluid, and the introduction of nano materials increases the cross-linking sites, thereby significantly improving the strength of the cross-linked gel.
[0041] The implementation of the 180°C high temperature resistant multi-stage cross-linking organic boron cross-linking agent and its preparation method of the present invention has the following beneficial effects:
[0042] (1) The method of the present invention grafts and copolymerizes the surface of a boron-containing polymer monomer onto the surface of a nanomaterial to obtain a boron-containing small molecule polymer, and then uses a variety of chelating agents to chelate the boron-containing small molecule polymer, borate esters, boron-containing compounds, etc. step by step to obtain an organic boron crosslinking agent. After the crosslinking agent is compounded with the fracturing fluid, the boron carriers with different release rates are opened layer by layer, releasing borate ions to cross-link with the fracturing fluid at multiple stages, and slowly forming a gel. The introduction of unique nanomaterials enhances the spatial structure and mechanical stability of the gel, and the temperature resistance of the fracturing fluid is greatly improved.
[0043] (2) Any of the first intermediate, the second intermediate, the third intermediate and the final product can be used as an organic boron crosslinking agent, and from the first intermediate to the final product, the crosslinking agent's delay performance, crosslinking strength and crosslinking fracturing fluid performance are gradually improved;
[0044] (3) By chelating boron-containing small molecule polymers, borate esters, boron-containing compounds, etc. step by step, the bonding probability between boron ions and hydroxypropyl guar gum is reduced, the cross-linking speed is controllable, and the delayed cross-linking time of the final product is adjustable by 2 to 5 minutes, thereby greatly reducing the friction of the fracturing fluid in the wellbore;
[0045] (4) The boron crosslinking agent crosslinked gel prepared by the present invention can withstand a high temperature of 180°C. When sheared for 120 min at 180°C and 170s-1, the apparent viscosity is stable at more than 100 mPa·s, and has good temperature and shear resistance. The gel can be completely broken, and the viscosity of the broken gel liquid is less than 5 mPa·s.
[0046] (5) The multi-stage cross-linked organic boron cross-linking agent prepared by the present invention has been applied in a repeated fracturing well in Jiaoshi, Chongqing, and has effectively solved the problem of high friction resistance of the fracturing fluid caused by small-sized casing fracturing in the rebuilt wellbore repeated fracturing well, and the effect of increasing fracturing production and speed is significant. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] The present invention will be further described below with reference to the accompanying drawings and embodiments, in which:
[0048] Figure 1 A schematic diagram of the cross-linking agent guar gum fracturing fluid provided by the present invention;
[0049] Figure 2 This is the 180°C temperature and shear resistance test curve of the cross-linking agent guar gum fracturing fluid provided by the present invention;
[0050] Figure 3 The friction performance test curve of the cross-linking agent cross-linked guar gum fracturing fluid provided by the present invention;
[0051] Figure 4 This is a curve diagram of the on-site construction of the cross-linking agent provided by the present invention. DETAILED DESCRIPTION
[0052] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, specific embodiments of the present invention are now described in detail with reference to the accompanying drawings.
[0053] The preferred embodiments of the present invention are described below in conjunction with the accompanying drawings. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention. Unless otherwise specified, the performance evaluation experimental conditions and experimental methods involved in the embodiments are all based on "SY / T 5107-2005 Water-based Fracturing Fluid Performance Evaluation Method" and "SY / T6216-1996 Fracturing Cross-linking Agent Performance Experiment Method".
[0054] Unless otherwise specified, the chemicals involved in the examples are all industrial grade and can be obtained by conventional means.
[0055] Example 1
[0056] The preparation scheme 1 of the multi-stage cross-linking organic boron cross-linking agent resistant to high temperature of 180° C. provided by the present invention is as follows:
[0057] S1: Preparation of the first intermediate:
[0058] Add 15 parts of ethylene glycol and 0.5 parts of nano-fumed silica to an enameled reactor, stir evenly and then disperse by ultrasonic oscillation for 15 minutes to obtain a ligand-solvent suspension; add 1 part of allyltriethoxysilane to the reactor, react for 1 hour at a reactor temperature of 20°C and a stirring speed of 300r / min to modify the surface of the first ligand; maintain the stirring speed unchanged, add 2 parts of fumaric acid, 3 parts of cis-propylene boric acid and 0.025 parts of potassium persulfate and sodium bisulfite (the ratio of the two is 3:2) to the solution, react at 35°C for 2 hours, and obtain a first intermediate by surface graft polymerization;
[0059] S2: Preparation of the second intermediate:
[0060] Add 2 parts of n-butanol, 10 parts of trimethyl borate and 3.9 parts of Schiff base to the batching kettle, react for 1 hour at a temperature of 60°C and a stirring speed of 200 r / min, transfer all the reaction products in the batching kettle to an enamel reactor, add 9.1 parts of Schiff base, mix well with the first intermediate, and react for 1 hour at a temperature of 60°C and a stirring speed of 300 r / min to obtain a second intermediate;
[0061] S3: Preparation of the third intermediate:
[0062] The reactor temperature was set at 70°C and the stirring speed was 700 r / min. 16 parts of polyvinyl alcohol were slowly added to the second intermediate, and the mixture was fully stirred and dissolved. The mixture was reacted at a stirring speed of 300 r / min for 1 hour to obtain a third intermediate.
[0063] S4: Final product preparation:
[0064] Keeping the temperature and stirring speed of the reactor unchanged, add 2 parts of sodium borate to the third intermediate, stir and mix to dissolve, add 4 parts of polyvinyl alcohol, continue to react for 1 hour, add water to dilute, obtain the final product, cool and discharge, which is the multi-stage cross-linked organic boron cross-linking agent resistant to high temperature of 180°C.
[0065] Example 2
[0066] The preparation scheme 2 of the multi-stage cross-linking organic boron cross-linking agent resistant to high temperature of 180°C provided by the present invention is as follows:
[0067] S1: Preparation of the first intermediate:
[0068] 18 parts of ethanol and 1 part of nano-graphene oxide were added to an enamel reactor, and the mixture was stirred evenly and then dispersed by ultrasonic oscillation for 20 minutes to obtain a ligand-solvent suspension; 1.5 parts of vinyl tri(2-methoxyethoxy)silane were added to the reactor, and the reaction was carried out for 1.5 hours at a reactor temperature of 20° C. and a stirring speed of 400 r / min to modify the surface of the nano-graphene oxide; while maintaining the stirring speed unchanged, 3 parts of maleic acid, 4 parts of 1-butene boric acid and 0.021 parts of potassium persulfate and sodium bisulfite (the ratio of the two was 3:2) were added to the solution, and the mixture was reacted at 40° C. for 2.5 hours to obtain a first intermediate by surface graft polymerization;
[0069] S2: Preparation of the second intermediate:
[0070] Add 3 parts of isopropanol, 12 parts of triethyl borate and 6 parts of triethanolamine to the batching kettle, react at a temperature of 65°C and a stirring speed of 300 r / min for 1 hour, transfer all the reaction products in the batching kettle to an enamel reactor, add 9 parts of triethanolamine, mix evenly with the first intermediate, and react at a temperature of 65°C and a stirring speed of 400 r / min for 1 hour to obtain a second intermediate;
[0071] S3: Preparation of the third intermediate:
[0072] The reactor temperature was set at 75°C and the stirring speed was 800 r / min. 22.5 parts of pinacol were slowly added to the second intermediate, and the mixture was stirred and dissolved. The mixture was reacted at a stirring speed of 350 r / min for 1.5 h to obtain a third intermediate.
[0073] S4: Final product preparation:
[0074] Keeping the temperature and stirring speed of the reactor unchanged, add 3 parts of boric acid to the third intermediate, stir and mix to dissolve, add 2.5 parts of pinacol, continue to react for 1.5 hours, add water to dilute, obtain the final product, cool and discharge, which is the multi-stage cross-linked organic boron cross-linking agent resistant to high temperature of 180°C.
[0075] Example 3
[0076] The optimization scheme of the multi-stage cross-linking organic boron cross-linking agent resistant to high temperature of 180°C provided by the present invention is as follows:
[0077] S1: Preparation of the first intermediate:
[0078] Add 16 parts of methanol and 0.8 parts of nano-fumed silica to an enamel reactor, stir evenly and then disperse by ultrasonic oscillation for 30 minutes to obtain a ligand-solvent suspension; add 1.2 parts of allyltriethoxysilane to the reactor, react for 2 hours at a reactor temperature of 25°C and a stirring speed of 350r / min to modify the surface of the nano-fumed silica; maintain the stirring speed unchanged, add 2.5 parts of fumaric acid, 3.5 parts of allylboronic acid pinacol ester and 0.021 parts of potassium persulfate and sodium bisulfite (the ratio of the two is 3:2) to the solution, react at 35°C for 3 hours, and obtain a first intermediate by surface graft polymerization;
[0079] S2: Preparation of the second intermediate:
[0080] Add 2.5 parts of isopropanol, 11.5 parts of triisopropyl borate and 4.2 parts of sodium gluconate to the batching kettle, react for 1.5 hours at a temperature of 60°C and a stirring speed of 300 r / min, transfer all the reaction products in the batching kettle to an enamel reactor, add 7.8 parts of triethanolamine, mix well with the first intermediate, and react for 1.5 hours at a temperature of 70°C and a stirring speed of 300 r / min to obtain a second intermediate;
[0081] S3: Preparation of the third intermediate:
[0082] The reactor temperature was set at 80°C and the stirring speed was 700 r / min. 17.85 parts of sorbitol were slowly added to the second intermediate, and the mixture was stirred and dissolved. The mixture was reacted for 1.5 hours at a stirring speed of 400 r / min to obtain a third intermediate.
[0083] S4: Final product preparation:
[0084] Keeping the temperature and stirring speed of the reactor unchanged, add 3 parts of borax to the third intermediate, stir and mix to dissolve, add 3.15 parts of sorbitol, continue to react for 1.5 hours, add water to dilute, obtain the final product, cool and discharge, which is the multi-stage cross-linked organic boron cross-linking agent resistant to high temperatures of 180°C.
[0085] The product obtained by this scheme is a reddish brown liquid with the best performance test. Therefore, this product is used as a multi-stage cross-linked organic boron cross-linking agent that can withstand high temperatures of 180°C. It is replaced by JBC-1 below, which is mixed with hydroxypropyl guar fracturing fluid in proportion to prepare the corresponding hydroxypropyl guar jelly fracturing fluid.
[0086] Example 4
[0087] The preparation method of hydroxypropyl guanidine jelly is as follows:
[0088] (1) slowly adding hydroxypropyl guar gum to 100 parts by weight of water under stirring to mix, adjusting the pH value to 11 with a 30% sodium hydroxide aqueous solution, and stirring for 30 minutes to obtain a hydroxypropyl guar gum aqueous solution;
[0089] (2) The hydroxypropyl guar gum was allowed to stand at 35° C. for 2 hours, and then a certain proportion of the organic boron crosslinking agent prepared in Example 3 was added thereto, and the mixture was stirred and mixed to obtain a hydroxypropyl guar gum jelly (fracturing fluid). The prepared jelly solution was as follows: Figure 1 As shown, it can be seen from the figure that the liquid is uniform and the jelly strength is strong.
[0090] Example 5
[0091] Performance Testing
[0092] (1) Cross-linking performance test
[0093] ① The guar fracturing fluid base fluid and jelly were prepared according to Example 4, and the crosslinking time and performance of hydroxypropyl guar were tested at different crosslinking agent dosages when the hydroxypropyl guar concentration was 0.5%. The experimental data are shown in Table 1.
[0094] It can be seen from Table 1 that the organic boron crosslinking agent synthesized in the present invention has a wider range of crosslinking agent concentrations than ordinary organic boron crosslinking agents. Because it adopts a multi-level chelation method, the release of the crosslinking agent is a slow process. As the amount of crosslinking agent added increases, the borate ions chelated in the outermost layer are still released, so there will be no over-crosslinking phenomenon. The state of the crosslinked gel with ordinary crosslinking agents is prone to over-crosslinking as the concentration of the crosslinking agent increases, and it is sensitive to the concentration of the crosslinking agent used. In addition, the first intermediate, the second intermediate, and the third intermediate synthesized in Example 3 can all crosslink hydroxypropyl guar gum.
[0095] Table 1 shows the crosslinking performance test results of the crosslinking agent under different addition conditions
[0096]
[0097] ② The guar gum fracturing fluid base fluid and the jelly were prepared according to Example 4, and the delayed crosslinking performance, crosslinking strength and temperature resistance of the crosslinking agent were tested. The experimental data are shown in Table 2.
[0098] It can be seen from Table 2 that the organic boron crosslinking agent synthesized by the present invention can achieve effective crosslinking of low-concentration hydroxypropyl guar fracturing fluid. When the concentration of hydroxypropyl guar is 0.13% to 0.65%, a gel with a large crosslinking strength can be formed, and the crosslinking time can be adjusted from 2 to 5 minutes, and the maximum temperature resistance is 180°C. It can be seen that the crosslinked fracturing fluid system crosslinked by the crosslinking agent of the present invention has good delayed crosslinking, hanging performance and temperature resistance.
[0099] Table 2 is the test results of crosslinking agent performance
[0100]
[0101] (2) Heat and shear resistance
[0102] The guar gum fracturing fluid base fluid and gel were prepared according to Example 4. The guar gum concentration was 0.65%, the cross-linking agent JBC-1 was added in an amount of 0.45%, and the heat and shear resistance was monitored by a MARS60 high temperature rheometer. The rheological curve was tested as shown in Figure 1 shown.
[0103] It can be seen from the rheological test curve of the fracturing fluid that the cross-linking agent provided by the present invention is slowly released layer by layer during the heating process, multiple cross-linking occurs during the process, and the viscosity of the fracturing fluid has multiple peaks, indicating that the cross-linking agent has good peeling release performance, and the online cross-linking time can be controlled and adjusted. After 170s -1 After continuous shearing, the viscosity of the fracturing fluid is finally greater than 50 mPa·s, indicating that the fracturing fluid of this embodiment has good temperature resistance and shear resistance and is suitable for reservoirs below 180°C.
[0104] (3) Drag reduction performance
[0105] The guar gum fracturing fluid base fluid and jelly were prepared according to Example 4.
[0106] Use a multifunctional flow loop instrument or similar products to measure the stable pressure difference when several liquids pass through the pipeline. When measuring the friction resistance of the fracturing fluid, it is necessary to clean it with clean water before changing the liquid.
[0107] First, prepare the fracturing fluid base fluid and pour it into the base fluid tank of the multifunctional flow loop instrument. Turn on the multifunctional flow loop instrument and set the flow rate to 30L / min. Immediately add the cross-linking agent to the base fluid tank in proportion. Start timing, record the pressure difference changes at different times, and calculate the resistance reduction rate. The test results are shown in Figure 2 This is used to simulate the friction change during the cross-linking process of the fracturing fluid to verify the great contribution of delayed cross-linking to the resistance reduction performance of the fracturing fluid.
[0108] from Figure 2It can be seen from the experimental data that the present invention adopts a multi-stage chelating cross-linking agent with delayed cross-linking performance. The delayed cross-linking time of the fracturing fluids of several groups of formulations is about 2 to 5 minutes, and the drag reduction rate changes little within 2 minutes. This reduces the friction resistance of the fracturing fluid as much as possible, controls the fracturing fluid not to cross-link in the wellbore, and will inevitably not cause high friction resistance to the construction.
[0109] (4) Gel breaking performance
[0110] The guar gum fracturing fluid base fluid and gel were prepared according to Example 4. Evaluation of the fracturing fluid gel breaking performance, the gel breaking time and residue content of several groups of liquids were tested, and the test results are shown in Table 3.
[0111] Table 3 Basic data test of fracturing fluid degelling fluid
[0112]
[0113] The experimental results show that the cross-linked gel provided by the cross-linking agent of the present invention can be completely broken under different temperature conditions, with a short breaking time and low viscosity of the broken gel liquid; the residue content of the broken gel liquid is as low as below 300 mg / L, meeting the industry standard (600 mg / L) requirements.
[0114] On-site construction example of the multi-stage cross-linking organic boron cross-linking agent provided by the present invention:
[0115] Jiaoye XX well is a well for repeated fracturing construction in the reconstruction wellbore. The construction well section is 2930.00-4116.00m, and the formation temperature is 141℃. The main difficulties faced are large pipe friction, limited sand ratio displacement, and narrow safety pressure window for fracturing construction. The multi-stage cross-linked organic boron cross-linking agent proposed in the present invention is used to prepare guar gum fracturing fluid as a pre-fluid. The overall construction friction is low (the resistance reduction rate calculated by construction data reaches 68.6%), and controlled fracture is achieved. The sand addition strength is effectively improved (the average sand addition strength is 2.05t / m), and the construction pressure is stable. Compared with the first domestically produced repeated fracturing well, the construction period is shortened from 32 days in the early stage of development to 20 days, and the project speed is increased by 60%. The typical construction curve is shown in Figure 4 Field practice has confirmed that the multi-stage cross-linked organic boron cross-linking agent provided by the present invention has good delayed cross-linking performance, can effectively reduce construction friction, and solve the difficulty of fracturing construction and sand adding.
[0116] The embodiments of the present invention are described above in conjunction with the accompanying drawings, but the present invention is not limited to the above-mentioned specific implementation modes, which are merely illustrative rather than restrictive. Under the guidance of the present invention, ordinary technicians in this field can also make many forms without departing from the scope of protection of the present invention and the claims, all of which are within the protection of the present invention.
Claims
1. A multi-stage cross-linking organic boron cross-linking agent resistant to high temperature of 180°C, characterized in that: The total weight of the components is 100: Boron-containing polymer monomer: 3-4 parts; Boric acid ester: 10-12 parts; Boron-containing compound: 2-3 parts; Solvent 1: 15-18 parts; Solvent 2: 2-3 parts; First ligand: 0.5-1 part; Second ligand: 13-15 parts; The third ligand: 20-25 parts; Alkenyl oxygen-containing silane: 1 to 1.5 parts; Strong hydrophilic monomer: 2-3 parts; Initiator: 0.015-0.035 parts; The remainder was deionized water.
2. The multi-stage cross-linking organic boron cross-linking agent resistant to high temperature of 180°C according to claim 1, characterized in that: The boron-containing polymer monomer is any one of allylboronic acid pinacol ester, vinylboronic acid pinacol ester, 1-phenylvinylboronic acid, cis-propyleneboronic acid, 3-vinylbenzeneboronic acid or 1-buteneboric acid.
3. The multi-stage cross-linking organic boron cross-linking agent resistant to high temperature of 180°C according to claim 1, characterized in that: The borate ester is any one of trimethyl borate, triethyl borate or triisopropyl borate.
4. The multi-stage cross-linking organic boron cross-linking agent resistant to high temperature of 180°C according to claim 1, characterized in that: The boron-containing compound is any one of borax, boric acid or sodium borate.
5. The multi-stage cross-linking organic boron cross-linking agent resistant to high temperature of 180°C according to claim 1, characterized in that: The first ligand is one of nano graphene oxide and nano fumed silica; The second ligand is any one of monoethanolamine, triethanolamine, ethylenediamine, acetylacetone, Schiff base, sodium gluconate, citric acid, diethylenetriaminepentaacetic acid, and N-hydroxyethylenediamine; The third ligand is any one of pinacol, xylitol, mannitol, sorbitol and polyvinyl alcohol.
6. The multi-stage cross-linking organic boron cross-linking agent resistant to high temperature of 180°C according to claim 1, characterized in that: The first solvent is one of methanol, ethanol and ethylene glycol; the second solvent is one of isopropanol and n-butanol.
7. The multi-stage cross-linking organic boron cross-linking agent resistant to high temperature of 180°C according to claim 1, characterized in that: The alkenyl oxygen-containing silane is any one of dimethylvinylethoxysilane, methylvinyldiethoxysilane, allyltriethoxysilane and vinyltri(2-methoxyethoxy)silane.
8. The multi-stage cross-linking organic boron cross-linking agent resistant to high temperature of 180°C according to claim 1, characterized in that: The strong hydrophilic monomer is one of fumaric acid and maleic acid.
9. The multi-stage cross-linking organic boron cross-linking agent resistant to high temperature of 180°C according to claim 1, characterized in that: The initiator is a combination system of potassium persulfate and sodium bisulfite, and the mass ratio of potassium persulfate to sodium bisulfite is 3:
2.
10. A method for preparing the multi-stage cross-linking organic boron cross-linking agent resistant to high temperature of 180°C as claimed in claim 1, characterized in that: The following steps are involved: S1: Preparation of the first intermediate: Add solvent 1 and the first ligand to the enamel reaction kettle, stir evenly and then perform ultrasonic oscillation dispersion for 15 minutes to 30 minutes to obtain a ligand-solvent suspension; add alkenyl oxygen-containing silane to the reaction kettle, react for 1 hour to 2 hours at a reaction kettle temperature of 20°C to 25°C and a stirring speed of 300r / min to 400r / min to perform surface modification on the first ligand; maintain the stirring speed unchanged, add a strong hydrophilic monomer, a boron-containing polymerization monomer and an initiator to the solution, react at 35°C to 40°C for 2 to 3 hours, and obtain a first intermediate by surface graft polymerization; S2: Preparation of the second intermediate: Add solvent 2, borate ester and W1 weight of the second ligand into the batching kettle, react for 1h to 1.5h at a temperature of 60°C to 70°C and a stirring speed of 200r / min to 300r / min, transfer all the reaction products in the batching kettle into an enamel reactor, add W2 weight of the second ligand, mix well with the first intermediate, react for 1h to 1.5h at a temperature of 60°C to 70°C and a stirring speed of 300r / min to 400r / min to obtain a second intermediate; S3: Preparation of the third intermediate: The reactor temperature is set at 70°C to 80°C, the stirring speed is 700r / min to 800r / min, and the third ligand by weight W3 is slowly added to the second intermediate, and the mixture is stirred and dissolved. The mixture is reacted at a stirring speed of 300r / min to 400r / min for 1h to 1.5h to obtain the third intermediate; S4: Final product preparation: Keeping the temperature and stirring speed of the reactor unchanged, add the boron-containing compound to the third intermediate, stir and mix to dissolve, add W4 weight of the third ligand, continue to react for 1h to 1.5h, add water to dilute, obtain the final product, cool and discharge, which is the multi-stage cross-linked organic boron cross-linking agent resistant to high temperature of 180°C; The ratio of W1 to W2 in the step S2 is 3:7 to 4:6; the ratio of W3 in the step S3 to W4 in the step S4 is 8:2 to 9:1.
Citation Information
Patent Citations
A boron cross-linking agent and its use in preparing boron cross-linked fracturing fluid suitable for high-temperature deep wells
CN104893705B
Preparation method of organic boron cross-linking agent, cross-linking agent and guanidine gum fracturing fluid
CN118206735A
Delayed borate crosslinked fracturing fluid having increased temperature range
US5445223A
Cited By
Novel thickening agent for oil well fracturing and preparation method thereof
CN119842379A
Quick-curing polyurethane seamless expansion joint material for roads and preparation method thereof
CN121022087A
Low-temperature activated nano-composite cross-linking agent, fracturing fluid, and preparation method and application of low-temperature activated nano-composite cross-linking agent and fracturing fluid
CN121991679A
A low-temperature activated nanocomposite crosslinking agent, fracturing fluid, preparation method and application
CN121991679B
Salt-resistant and temperature-resistant thickening agent for oil field fracturing fluid and preparation method of thickening agent
CN122587691A